2018
DOI: 10.1039/c8dt00464a
|View full text |Cite
|
Sign up to set email alerts
|

Formation of bimetallic metal–organic framework nanosheets and their derived porous nickel–cobalt sulfides for supercapacitors

Abstract: Metal-organic frameworks (MOFs) show great advantages as new kinds of active materials for energy storage. In this study, bimetallic metal-organic frameworks (Ni/Co-MOFs) with nanosheet-assembled flower-like structures were synthesized by etching Ni-MOF microspheres in a cobalt nitrate solution. It can be clearly observed that the amount of Co(NO3)2 and etching time play crucial roles in the formation of Ni/Co-MOF nanosheets. The Ni/Co-MOFs were used as electrode materials for supercapacitors and the optimized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(55 citation statements)
references
References 44 publications
1
54
0
Order By: Relevance
“…Supercapacitors are a new generation of energy storage device that not only has high charge‐discharge efficiency, power density, reliability and long cycle lifetime similar to traditional capacitors, but also has high energy density close to batteries . In supercapacitor assemblies, electrode materials are a critical component affecting device performances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supercapacitors are a new generation of energy storage device that not only has high charge‐discharge efficiency, power density, reliability and long cycle lifetime similar to traditional capacitors, but also has high energy density close to batteries . In supercapacitor assemblies, electrode materials are a critical component affecting device performances.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, metal‐organic frameworks (MOFs) have attracted extensive attentions as energy storage materials, especially, supercapacitor electrode materials . MOFs are a porous crystalline material self‐assembled by coordination reactions between transition metal ions and organic ligands containing multiple carboxyl groups or nitrogen electrondonors .…”
Section: Introductionmentioning
confidence: 99%
“…[27,28] It has been proved that the electrochemical behavior of an electrode is affected by the morphology and structure of its materials. [29,30] Accordingly, scientists introduced different types of architectures such as nanowires, [31] nanosheets, [32] and nanotubes, [33] which reflected high Cs owing to their exclusive porous networks and remarkable surface area (SA). Among which, nanosheet arrays have reflected excellent potential as desirable electrode materials for ESDs owing to their exclusive structural merits containing rich reaction sites and shortened diffusion pathways for quick charge and discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [20] reported synthesis of a Zndoped Ni-MOF with capacitances of 1620 and 860 F g − 1 were achieved at 0.25 and 10 A g − 1 , respectively, and the retention was kept at 91% even after 3000 cycles for MOF sample with a Zn/Ni of 0.26. Chen et al [21] have prepared bimetallic Ni/Co-MOFs with nano-sheet assembled ower-like morphology with high speci c capacitance of 1220.2 F g − 1 at 1 A g − 1 and high capacitance retention of 87.8% after 3000 cycles. Xia et al have developed a kind of Ni/Co-MOF with ake-assembled spherical microstructures, which had a capacitance of 530.4 F g − 1 at 0.5 A g − 1 and almost no capacity attenuation after 2000 charge/discharge cycles [22].…”
Section: Introductionmentioning
confidence: 99%